The Prevalence of Drug Use Among High School Students and Affecting Factors: A Community-Based Cross-Sectional Study - Sütlü, Sevinç; Til, Ayşen; Kılınç, Ahmet Selçuk (Addicta: The Turkish Journal on Addictions, 2021)
The present study aimed to determine the prevalence of drug use, sociodemographic characteristics, and risk factors among high school students and yield a grounding for further studies. The data of the present cross-sectional study were collected through the questionnaires filled out by the students under the supervision of the staff of a Public Health Directorate. Among a total of 12,935 high school students in Burdur city, 2,112 students were selected using the stratified random sampling method with the prevalence 50%, margin of error 2%, and type 1 error 5%. 2011 students responded to the survey questions. The data were analyzed using the SPSS 15.0 package program. The students tried tobacco (45.3%), alcohol (33.0%), and drugs (3.7%) at least once in their lifetime. Previous employment or current employment (OR: 14.905 CI: [5.140-43.229]), low income (OR: 2.545 CI: [1.338-4.843]), tobacco use (OR: 5.575 CI: [1.640-18.952]), alcohol use (OR: 14.905 CI: [5.140-43.229]), and drug user in the family (OR:10.242 CI: [3.281-31.975]) were identified as factors increasing the risk of drug use. The rate of drug use experience among high school students is similar to the related data of Turkey. Tobacco and alcohol use come before drug use.